Предмет: Математика,
автор: katyvip0206
7x-(3+2x)=x+9
13-(2x-5)=x-3
3x-(10-9x)=22x
26-(17-2x)=5x
5(3-2y)-4(9-y)=3(y+5)
14(2x-3)-5(x+4)=2(3x+5)+5x
9(3x-7)+3(8x-11)=3(9x+8)
6(7x-11)-13(x-6)=14(2x+1)
Решите пожалуйста!
Заранее спасибо!
Ответы
Автор ответа:
0
1)7х-(3+2х)=х+9
7х-3-2х=х+9
5х-х=9+3
4х=12
х=
=3
2)13-(2х-5)=х-3
13-2х+5=х-3
-2х-х=-18-3
-3х=-21
х=
=7
3)3х-(10-9х)=22х
3х-10+9х=22х
12х-22х=10
-10х=10
х=
=-1
4)26-17+2х=5х
2х-5х=-9
-3х=-9
х=
=3
5)5(3-2у)-4(9-у)=3(у+5)
15-10у-36+4у=3у+15
-21-6у=3у+15
-6у-3у=21+15
-9у=36
у=
=-4
6)28х-42-5х-20=6х+10+5х
23х-6х-5х=42+20+10
12х=72
х=
=6
8)42х-66-13х-78=28х+14
29х-28х=66+14
Х=80
7х-3-2х=х+9
5х-х=9+3
4х=12
х=
2)13-(2х-5)=х-3
13-2х+5=х-3
-2х-х=-18-3
-3х=-21
х=
3)3х-(10-9х)=22х
3х-10+9х=22х
12х-22х=10
-10х=10
х=
4)26-17+2х=5х
2х-5х=-9
-3х=-9
х=
5)5(3-2у)-4(9-у)=3(у+5)
15-10у-36+4у=3у+15
-21-6у=3у+15
-6у-3у=21+15
-9у=36
у=
6)28х-42-5х-20=6х+10+5х
23х-6х-5х=42+20+10
12х=72
х=
8)42х-66-13х-78=28х+14
29х-28х=66+14
Х=80
Автор ответа:
0
Спасибо!
Автор ответа:
0
Не за что)
Похожие вопросы
Предмет: Информатика,
автор: irinaoa
Предмет: Алгебра,
автор: UnicornIra
Предмет: Математика,
автор: 89247660605l
Предмет: Математика,
автор: Polina19129